Chylothorax in a neonate: a case report - Shodikin, Muhammad Ali; Hadi Khoiruddin, Mukhammad Arif; Bellynda, Wynne (Indonesian Pediatric Society, 2025)
Chylothorax is rare in neonates but can be fatal if not diagnosed and appropriately managed. We report a baby boy diagnosed with chylothorax, which showed significant improvement after the installation of indwelling pleural catheters (IPC).